2018
DOI: 10.1038/s41598-018-20571-2
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin-10 (KP-10) stimulates osteoblast differentiation through GPR54-mediated regulation of BMP2 expression and activation

Abstract: Kisspeptin-10 (KP-10) acts as a tumor metastasis suppressor via its receptor, G-protein-coupled receptor 54 (GPR54). The KP-10-GPR54 system plays an important role in embryonic kidney development. However, its function in osteoblast differentiation is unknown. Osteoblast differentiation is controlled by a range of hormones and cytokines, such as bone morphogenetic protein (BMPs), and multiple transcription factors, such as Runt-related transcription factor 2 (Runx2), alkaline phosphatase (ALP), and Distal-less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 36 publications
(49 reference statements)
0
21
0
Order By: Relevance
“…MG63 cells were transiently transfected with the indicated plasmids using Lipofectamine 2000 (Invitrogen, Carlsbad, CA), as described previously 37 . Cells were harvested 24 h after transfection.…”
Section: Methodsmentioning
confidence: 99%
“…MG63 cells were transiently transfected with the indicated plasmids using Lipofectamine 2000 (Invitrogen, Carlsbad, CA), as described previously 37 . Cells were harvested 24 h after transfection.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have found that miR-17, miR-27a, miR-140-5p and miR-654-5p can directly inhibit the expression of BMP2 to regulate osteogenic differentiation. 34 MiR-197-3p, as a member of miRNA family, can regulate the proliferation of tumor cells. 35 In this study, it was found that the expression of miR-197-3p in OVX group was increased.…”
Section: Discussionmentioning
confidence: 99%
“…Kisspeptin-10 (Kp-10) is a peptide hormone encoded by kiss 1 gene, which is synthesized by hydropthalamic neurons and play a variety of biological functions in the body through its receptor GPR54 [16]. Meanwhile, GPR54 regulates the release of GnRH and inhibits the synthesis of growth hormone [17,18].…”
Section: Introductionmentioning
confidence: 99%